AWARENESS AMONG PATIENTS REGARDING IMPLANTS AS A TREATMENT OPTION FOR REPLACEMENT OF MISSING TEETH AMONG RURAL POPULATION - Ravi Teja, Madulla; Ariga, Padma; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Regular oral conditions have appeared to substantially affect prosperity and quality of life. The loss of at least one common tooth often brings about incapacity, as basic day-to-day living exercises, for example, talking and eating, are hindered, and furthermore, in handicap, for instance, by diminished social communication as a result of humiliation related to dental replacement wearing. The primary characterization of prosthodontics is the restoration of function following tooth loss. The aim of the study was to understand awareness among rural patients about implants for replacing missing teeth.This survey was done among 100 subjects in rural zones using a self-administered questionnaire. The mean age of the participants was 36.5 years. Information pertaining to awareness of dental implants, reasons for replacement, and information sources over dental implants was obtained. The collected data were collected and analysed.Out of 100 subjects, 55 were males and 45 females. Around 35% of the subjects were aware of dental implants. 64% sought replacement for masticatory reasons, 32% for esthetic reasons, and 4% for phonetics. Dentists were the primary source of information about implants (73%), followed by mass media (15%) and friends (12%). The greater part of the participants were not aware with respect to implants, and not many had undergone implant treatment. It additionally demonstrated the requirement for giving more information to patients regarding this treatment modality.